The influence of IFRS and institutional quality on economic growth: empirical evidence in the GCC countries using panel ARDL analysis - Abdulwahab Mujalli; Mohammad Jibran Gul Wani; Ahmed Almgrashi; Irfan Ahmed; Nasser Asiri (Cogent Business & Management, 2024)
We empirically investigated the effect of international financial reporting standards (IFRS) and institutional quality (IQ) on economic growth in the GCC region. We used panel data collected over 25 years (1998–2022) from six GCC countries—Bahrain, the United Arab Emirates, Saudi Arabia, Qatar, Oman, and Kuwait. A panel cointegration test was used to investigate the relationships among the variables. This study confirms a long-run 15% decline in GDP following the adoption of IFRS in GCC nations. The short-term impact is positive, with a rise of 13% in the GDP. Conversely, institutional quality negatively affected the GDP in the long and short run. We used an index for institutional quality based on six variables. It is recommended that policymakers take advantage of the immediate advantages of adopting IFRS while implementing long-term plans to reduce the projected decline in GDP. The economic repercussions of IFRS adoption and institutional quality should be carefully considered while at the same time emphasizing the advantages of open trade and low inflation in encouraging long-term growth.
Keywords: 650; GCC; economic growth; IFRS; institutional quality; PMG; panel ARDL